Radiosensitizing effects of oroxylumind1cum extract on hela cells - Long, Nurin Afiqah Che (Universiti Sains Malaysia, 2017)
The main aims of radiotherapy to optimally eradicate tumours while sparing the normal tissue could be achieved with the combination treatment using natural products based medicinal plants. Oroxylum Indicum (Ol) is a Malaysian consumable plant with a variety of health attributes that contains useful biocompound that serves as anticancer agent. In this study, the potentials of OI extracts to increase cells radiosensitivity towards radiotherapy were investigated. The cytotoxic effects of OI extracts were initially determined in-vitro using HeLa cells. The cells with non-toxic concentration of OI extracts were irradiated with 6 MV and 10 MV photon beams. The cell survivals were evaluated using colorimetric and clonogenic assay. The cell survival curves were then analysed using Linear Quadratic model. The OI extracts with the tested concentration are found nontoxic to HeLa cells. The combination of OI extracts and irradiation are found to reduce the cells survival which indicates radiosensitization effects. The radiosensitization observed and calculated are found to be more than 3 folds. Radiobiological analysis shows inconsistent results with increase alpha value for most samples with OI extracts and random beta value. The OI extracts are found to induce radiosensitization in HeLa cancer cells when irradiated with megavoltage photon beams. This study indicates the potential of plant based natural product to be applied to increase therapeutic efficiency in radiotherapy.